2011
DOI: 10.1167/iovs.10-6646
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravitreal Injection of Bevacizumab on Retinal Circulation in Patients with Neovascular Macular Degeneration

Abstract: Arteriolar diameter decreased significantly after the first injection and persisted until the end of the study suggesting a long-term effect of bevacizumab on vascular tone. However, the blood flow change is not significant. A borderline significant decrease in neuroretinal rim perfusion was observed and suggests that the neuroretinal rim may be more sensitive than the peripapillary retina to the effects of bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
4
40
2
Order By: Relevance
“…Our findings contrast findings from previous studies [10][11][12] looking at vasculature changes following anti-VEGF treatment in neovascular AMD, where a significant decrease in arteriolar diameter at 3 months and 1 year was seen. These studies, however, had significant limitations, given that only arteriolar calibre was assessed and the lack of a control group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contrast findings from previous studies [10][11][12] looking at vasculature changes following anti-VEGF treatment in neovascular AMD, where a significant decrease in arteriolar diameter at 3 months and 1 year was seen. These studies, however, had significant limitations, given that only arteriolar calibre was assessed and the lack of a control group.…”
Section: Discussioncontrasting
confidence: 99%
“…11 A more recent study on 23 patients also found decreased retinal arteriolar diameter during the course of initial anti-VEGF injections for neovascular AMD. 12 No significant change in blood flow was observed. All these studies, however, were limited by a lack of a control group.…”
Section: Introductionmentioning
confidence: 89%
“…Using a bidirectional laser Doppler flowmeter, Fontaine et al [23] demonstrated that the baseline retinal arteriolar diameters decreased significantly after the first BEV injection and persisted until the fifth week after the third BEV dose. During the study period, the authors did not observe any alterations in retinal blood flow in 23 eyes of 23 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are even some reports on a fellow-eye treatment effect for intravitreal RAN and BEV [31,32] . None of the prior vessel diameter studies [19][20][21]23] , except 1 [22] , presented any results pertaining to noninjected fellow eyes following anti-VEGF delivery. Intravitreal RAN did not induce any alterations in vessel caliber in the noninjected eyes [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a major increase of RBFV occurring in arterioles supports the theory of vasoconstriction being the major driver of increase in RBFV. 20,21 In this set of patients, we found only a weak association between changes in IOP and blood flow velocity (data not shown). We therefore conclude that changes in RBFV were not substantially affected by changes in IOP.…”
Section: Main Findingsmentioning
confidence: 64%